Experimental investigation on total-ionizing-dose radiation effects on the electrical properties of SOI-LIGBT. (January 2021) - Yang, Guangan; Wu, Wangran; Zhang, Xingyao; Tang, Pengyu; Yang, Jing; Zhang, Long; Liu, Siyang; Sun, Weifeng
Highlights: We examined the response of out-put current under the TID irradiation for the Lateral IGBT via experiment and simulation. At the same Vov, ICE increases at small VCE and decreases at high VCE after irradiation were observed firstly. The abnormal TID irradiation effects are attributed to the bipolar transport of the SOI-LIGBT. The degradation mechanisms of SOI-LIGBT under TID irradiation were demonstrated by analysis and simulation. Abstract: In this paper, the experimental investigation on the electrical properties of silicon-on-insulator lateral insulated-gate bipolar transistor (SOI-LIGBT) after total-ionizing-dose (TID) irradiation is presented. We find that the TID irradiation reduces the threshold voltage (Vth ), and increases the collector current (ICE ) at the same gate voltage (Vg ). The raising ICE is mainly attributed to the negative shift of the Vth . However, at the same overdrive voltage (Vov = Vg − Vth ), the ICE at small VCE increases and the ICE at high VCE decreases after irradiation. The distinctive response of the out-put characteristics after irradiation is ascribed to the positive trapped charges in the field oxide (FOX) layer and the buried oxide (BOX) layer. The inimitable out-put behavior occurs at whatever the sign of the gate bias voltage during irradiation. The degradation mechanisms of the TID effects on the SOI-LIGBT are further analyzed and confirmed by simulation.